O contrato de trabalho intermitente brasileiro: a necessidade de regulação por meio da negociação coletiva - Brolio, Raphael Jacob (2018)
The main objective of the paper is to show the need for collective bargaining to regulate the Brazilian labor contract (intermittent mode), considering the current national legislation, which is scarce and precarious regarding the matter